The effect of profitability and thin capitalization on tax avoidance moderated by transfer pricing in energy sector companies listed on The Indonesia Stock Exchange - Wibowo, Aris Suko; Sari, Diana (WIM Solusi Prima, 2024)
The contribution of taxes to state revenue in Indonesia is very high. In 2021, 2022, and 2023, tax revenue contributed an average of 77.17 percent of total state income and grants, with 7.23 percent of tax revenue coming from the mining and quarrying sector. The tax burden on companies leads to efforts for tax avoidance. Several factors that influence tax avoidance are profitability, thin capitalization, and transfer pricing. This study aims to determine the effect of profitability and thin capitalization on tax avoidance moderated by transfer pricing. The research objects are companies in the energy sector listed on the Indonesia Stock Exchange for the period 2021 to 2023. The research method used is quantitative with secondary data sources. The sample size is 31 companies, observed over 3 years, resulting in 93 observations. Regression analysis was performed using the Eviews 12 software. The results show that profitability does not affect tax avoidance. Thin capitalization practices have a positive and significant effect on tax avoidance. Transfer pricing does not strengthen the relationship between profitability and tax avoidance. Transfer pricing does not strengthen the relationship between thin capitalization and tax avoidance.